What characteristics define individuals who serve as kataribe (storytellers) in conveying lessons derived from the unprecedented disaster, including the Fukushima Daiichi Nuclear Power Plant accident? - Matsunaga, Hitomi; Yamada, Shuji; Kashiwazaki, Yuya; Orita, Makiko; Takamura, Noboru (Frontiers in Communication, 2025)
On March 11, 2011, the triple tragedy of an earthquake, tsunami, and nuclear disaster struck Fukushima Prefecture. This study aimed to clarify the characteristics of kataribe (“storytellers”) who experienced the tragedy and conveyed their experiences in Fukushima, especially the struggle to continue as kataribe. A questionnaire survey was conducted from January 15 to July 30, 2024. The quantitative data were analyzed using chi-square tests and logistic regression analysis. The results indicated that most kataribe were satisfied with their current activities, expressed a strong desire to continue, and were highly motivated to improve their skills. However, approximately half of the respondents experienced difficulties in continuing as a kataribe. Moreover, they expressed a lack of confidence in themselves, social understanding, and economic support. The findings of this study highlight the importance of preserving diverse traditional resources, such as kataribe, who promote disaster prevention measures based on their experiences, not as experts but as peer supporters.